ТЕОРЕТИЧЕСКИЕ ОСНОВЫ АККУМУЛИРОВАНИЯ ЕСТЕСТВЕННОГО ХОЛОДА В ГРУНТОВОМ МАССИВЕ - Яхшибоев , Шухрат; Хамраев, Сардор; Узоқова, Юлдуз (Innovatsion texnologiyalar, 2022)
A mathematical model of heat exchange during cooling of a soil massif using a natural accumulator of cold soil (GANC) has been developed, the results of modeling an underground storage facility for storing fruits and vegetables with GANC, which is combined with an active ventilation system under non-stationary temperature conditions, are presented.